Determination of Total Levels of Secondary Metabolites and Oral Acute Toxicity Testing of Purple Leaf Ethanol Extract (PLEE) in Wistar Rats - Niluh Puspita Dewi; Miranti Miranti; Magfirah Magfirah; Athia Kurnia Kasim; I Made Dipayana (Journal of Public Health and Pharmacy, 2024)
Introduction: The use of traditional medicines derived from the active ingredients of several types of plants is preferred by the community in treating several types of diseases. One of the plants that has been used by the community as medicine is purple leaves with the Latin name Grapthophylum pictum (L.) Griff. These leaves are traditionally used to treat rheumatism, menstruation, hemorrhoids, urinary tract infections, scabies, swelling, wounds, dermatitis, ear diseases, laxatives, and cancer. The aim of this study was to determine the total levels of secondary metabolites from purple leaf extract ethanol (PLEE) and evaluate the effect of administering PLEE on acute toxicity (LD50) in Wistar rats. Methods: This research is a laboratory experiment with a post test only controlled group design. The research subjects were 20 male Wistar rats, divided into 1 control group and 3 treatment groups, each consisting of 5 rats. The control group only received distilled water, the Treatment I group (P1) was given a suspension of the purple leaf extract test preparation at a dose of 500 mg/kg. Treatment group II (P2), received a suspension of the test preparation at a dose of 2,000 mg/kg, while Treatment group III (P3) received a suspension of the test preparation at a high dose of 5,000 mg/kg of mice. The test preparation was given orally with only one administration at the beginning of the research period and observation was carried out for 14 days. Data was obtained if the rats died after being given treatment. Results: The results showed that the total secondary metabolite content of purple leaves was alkaloids (24,725.99 mg/g), saponins (89.191 mg/g), flavonoids (6.332 mg/g) and tannins (0.884 mg/g), while based on toxicity the PLEE classification was mildly toxic with an LD50 value of 3,890 mg/kg in accordance with BPOM RI's acute toxicity potential at toxicity level 4 (oral LD50 500 – 5,000 mg/kg). Conclusion: PLEE showed the highest total content of secondary metabolites in alkaloids, and consumption of PLEE in high doses caused the death of rats with a mild toxic classification.